Review of recent social policy reforms for a fair and competitive Europe - 2014 report of the Social Protection Committee (Luxembourg, 2015)
"This report presents the annual review of the Social Protection Committee on the development of social protection policies, including social inclusion, pension, health and long-term care, in the European Union. Focusing on policy measures adopted in the period 2013-2014, the report aims at assessing the main directions of reform efforts in the field of social protection. It is based on social reporting done by the Member States in the context of the National Social Reports. A thematic section is dedicated to youth exclusion as one of the foremost challenges to a social Europe arising from the economic crisis."